2021
DOI: 10.1186/s13065-021-00771-0
|View full text |Cite
|
Sign up to set email alerts
|

Active constituents of Zanthoxylum nitidium from Yunnan Province against leukaemia cells in vitro

Abstract: Zanthoxylum nitidium (Roxb.) DC (Rutaceae) is well known for inhibiting the proliferation of human gastric, liver, kidney and lung cancer cells, though research on its potential use in treating leukaemia is relatively rare. Twenty-six compounds were isolated from the chloroform and petroleum ether extracts of the roots and leaves of Z. nitidium (Zanthoxylum nitidium). They were ( +)-9′-O-transferuloyl-5, 5′-dimethoxylaricriresinol (1), 8-(3′-oxobut-1′-en-1′-yl)-5, 7-dimethoxy-coumarin (2), 5, 7, 8-trimethoxy-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A wide variety of benzophenanthridine alkaloids ( Figure 19 ) have been extracted by Deng, Y’s group [ 95 ] in Zanthoxylum avicennae from Yunnan Province, and their antileukemic cell line HLa activity in vitro is determined, with better activity of bocconoline ( 60 ), zanthoxyline ( 61 ), nitidine chloride ( 54 ), chelerythrine ( 2 ), and their IC 50 values (μM) in the order of 7.65 ± 0.11, 24.94 ± 1.99, 3.59 ± 0.82, and 15.52 ± 0.26. Nitidine chloride ( 54) results in significant S-phase arrest and induces apoptosis in HEL cells, thus becoming a promising potential antileukemic candidate.…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From N...mentioning
confidence: 99%
See 3 more Smart Citations
“…A wide variety of benzophenanthridine alkaloids ( Figure 19 ) have been extracted by Deng, Y’s group [ 95 ] in Zanthoxylum avicennae from Yunnan Province, and their antileukemic cell line HLa activity in vitro is determined, with better activity of bocconoline ( 60 ), zanthoxyline ( 61 ), nitidine chloride ( 54 ), chelerythrine ( 2 ), and their IC 50 values (μM) in the order of 7.65 ± 0.11, 24.94 ± 1.99, 3.59 ± 0.82, and 15.52 ± 0.26. Nitidine chloride ( 54) results in significant S-phase arrest and induces apoptosis in HEL cells, thus becoming a promising potential antileukemic candidate.…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From N...mentioning
confidence: 99%
“…Notably, buegenine (56) exhibits better activity against drug-resistant CEM/ADR5000 cell lines than doxorubicin [94]. A wide variety of benzophenanthridine alkaloids (Figure 19) have been extracted by Deng, Y's group [95] in Zanthoxylum avicennae from Yunnan Province, and their antileukemic cell line HLa activity in vitro is determined, with better activity of bocconoline ( 60 The natural product rhoifoline B ( 63) is structurally modified to obtain compound 65 (Figure 20) with the hydroxy substitutions at the 11-position. Compound 66 (Figure 20), originating from compound 65 through structural modification, enhances the inhibition selectivity of tyrosine DNA phosphodiesterase 1 (TDP1), with an IC50 value of 1.7 ± 0.24 µM.…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From R...mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies indicated that certain benzophenanthridine alkaloids showed strong inhibitory effects on leukemia cell lines [26,27]. To continue our research, two active benzophenanthridine alkaloids, chelerythrine (1) and sanguinarine (2) (Figure 1), which were found in high abundance, were selected as the starting compounds for structural modification to obtain antileukemia drug candidates with better activity.…”
Section: Introductionmentioning
confidence: 99%